Harmonisasi Gaya Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam Di MAN 2 Hulu Sungai Utara Plus Keterampilan - Raisa Nabilla; Falhi Azmi (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Students’ learning styles are an important factor influencing learning success. The problem addressed in this study is the diversity of students’ learning styles, namely visual, auditory, and kinesthetic, which requires teachers to implement adaptive instructional strategies and pay attention to students’ engagement in the classroom. This study aims to describe visual, auditory, and kinesthetic learning styles in Islamic Cultural History (SKI) subjects at MAN 2 Hulu Sungai Utara Plus Keterampilan. This research employed a qualitative approach, with data collected through interviews, observations, and documentation, involving the SKI teacher as the subject and students’ learning styles as the object. Data were analyzed using data reduction, data display, and verification within a descriptive qualitative framework. The results show that visual learners tend to prefer independent reading and writing activities, auditory learners are active in discussions and verbal repetition, while kinesthetic learners prefer interactive activities and have difficulty maintaining prolonged passive learning. Teachers facilitate these differences through lectures, question-and-answer methods, and visual media such as videos and PowerPoint for visual and auditory learners, as well as interactive activities and practical exercises for kinesthetic learners. These findings highlight the importance of aligning instructional strategies with students’ learning characteristics. Keywords: Learning Styles, Students, Islamic Cultural History Abstrak Gaya belajar siswa merupakan faktor penting yang mempengaruhi keberhasilan pembelajaran. Permasalahan dalam penelitian ini adalah keberagaman gaya belajar siswa yang meliputi visual, auditori, dan kinestetik, sehingga menuntut guru untuk menerapkan strategi pembelajaran yang adaptif dan memperhatikan keaktifan siswa di kelas. Penelitian ini bertujuan untuk mendeskripsikan gaya belajar visual, auditori, dan kinestetik pada mata pelajaran Sejarah Kebudayaan Islam (SKI) di MAN 2 Hulu Sungai Utara Plus Keterampilan. Penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi, dengan subjek guru SKI dan objek gaya belajar siswa. Analisis data dilakukan melalui reduksi data, penyajian data, dan verifikasi secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa siswa dengan gaya belajar visual cenderung menyukai membaca dan menulis secara mandiri, siswa auditori aktif dalam diskusi serta pengulangan verbal, sedangkan siswa kinestetik lebih menyukai aktivitas interaktif dan kurang mampu bertahan dalam pembelajaran pasif yang lama. Guru memfasilitasi perbedaan tersebut melalui metode ceramah, tanya jawab, serta penggunaan media visual seperti video dan PowerPoint untuk gaya visual dan auditori, serta kegiatan interaktif dan praktik langsung untuk gaya kinestetik. Temuan ini menunjukkan pentingnya penyesuaian strategi pembelajaran dengan karakteristik gaya belajar siswa. Kata Kunci: Gaya Belajar, Siswa, Sejarah Kebudayaan Islam